Women acceptance of episiotomy procedure before and after receiving educational materials: Pretest posttest study - Aseel K. Haji; Suha R. Elzahrany; Rozana I. Kamal; Alanood E. Sindi; Linah K. Khairou; Rahaf M. Alahmadi; Albagir M. Hassan (Elsevier, 2022)
Objectives: Episiotomy is a frequently performed surgical procedure by obstetricians and midwives during vaginal birth. It is defined as a surgical incision in the perineal area through the second stage of delivery. Therefore, this study aimed to evaluate women's acceptance toward episiotomy before and after providing education. Methods: A Quasi-experiment pretest posttest study was conducted on a total of 234 patients attending antenatal clinics in Maternity and Children hospital and Heraa General hospital in Makkah during June-August 2021. Participants were personally interviewed and provided with evidence-based information about the procedure then re-evaluated by the investigators. The statistical analysis was carried using Two Tailed Tests. Statistical significance was set on a P value of 0.05 or less. Results: Total of 234 participant fulfilling the inclusion criteria were interviewed. Females mean age is 26.2 ± 9.7 years. Exact of 115 (49.1%) women heard about episiotomy. And 79 (33.8%) correctly described it as a surgical incision. Also, 89 (38%) understood that it is not recommended for all, and 109 (46.6%) knew that anesthesia is required. The most reported source of information was internet/ social media (49%; 72), followed by friends/relatives (35.4%; 52). Before education, 112 (47.9%) would accept episiotomy if required which was significantly improved to be among 173 (73.9%) of them after receiving the educational materials. Conclusion: Due to the controversial opinions and practices of episiotomy, ensuring patients awareness and understanding is crucial. Providing correct information from trusted sources will help minimizing the chances of receiving inaccurate information from unreliable sources. Therefore, making wrong decisions, and refusing needed episiotomy. Health practitioners should be encouraged to discuss patients' concerns and correct their misconceptions.